3D nonlinear analysis of a composite steel/concrete viaduct - Pinheiro, Rui (2014)
In this paper it is studied the nonlinear behaviour of the composite steel-concrete Sousa river viaduct, located in A43 highway, Portugal. Used software to model such viaduct is ATENA®, which is a nonlinear structural analysis software that incorporates interface models. A 3D numerical model, that considers torsional effects, is developed. In order to validate this model, obtained data from developed load test as well as the results from a 2D model, developed in the same software ATENA®, will be used. Once the model is developed and calibrated, it is intended to process all obtained results, namely, overall deformation, maximum displacements, strengths and strains in all directions. The potentialities of a nonlinear 3D numerical model are therefore elicited.